Polyimide film

Polyimide films with tailored physical properties enable direct lamination of metal layers without adhesives, addressing the challenges of adhesion and dimensional stability in conventional methods, and achieving strong and stable adhesion even with thin metal layers.

JP2025037537APending Publication Date: 2025-03-18DUPONT TORAY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023144518
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-06
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Conventional polyimide films with adhesive layers face challenges in achieving sufficient adhesion with thin metal layers, particularly copper, due to the low heat resistance of the adhesive layer, which can lead to reduced dimensional accuracy and adhesion strength.

Method used

Development of polyimide films with specific physical properties, such as a glass transition temperature of 300° C. or less, loss tangent of 0.85 or less, and storage modulus ratios, which allow for direct lamination of metal layers without an adhesive layer, ensuring sufficient adhesion even with thin metal layers.

Benefits of technology

The polyimide films achieve strong and stable adhesion with metal layers, maintaining dimensional stability and adhesion strength even under high-temperature conditions, making them suitable for various electronic applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025037537000001
    Figure 2025037537000001
Patent Text Reader

Abstract

To provide a polyimide film that is useful for metal lamination and the like.SOLUTION: The glass transition temperature (Tg) of the polyimide film is 300°C or lower.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polyimide film and the like. [Background technology]

[0002] Due to its excellent heat resistance, chemical resistance, and electrical properties, polyimide film is widely used for applications such as electrical insulation material for electric wires, chip-on-film (COF), base film for flexible printed circuit boards (FPC), carrier tape film for tape automated bonding (TAB) of ICs, and tape for fixing IC lead frames.

[0003] As electronic devices become smaller, lighter, more functional, multifunctional and highly densely packed, the printed wiring boards used in these electronic devices are rapidly becoming denser as conductor widths and spaces between conductors become narrower, more multi-layered, more flexible and the substrates become thinner.

[0004] 2. Description of the Related Art Conventionally, flexible printed wiring boards having a three-layer structure in which a conductor layer (such as a copper layer) is bonded to a polyimide film via an adhesive layer have been known (Patent Document 1). [Prior art documents] [Patent documents]

[0005] [Patent Document 1] Patent No. 2680816 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide a polyimide film suitable for use in metal lamination (lamination of a metal layer) and the like. [Means for solving the problem]

[0007] As described above, a laminated film is known in which a metal layer (copper foil or the like) is bonded to a polyimide film via an adhesive layer.

[0008] However, such laminated films require the provision of an adhesive layer, and it may be difficult to reduce the thickness of the metal layer during lamination. In addition, there is a risk of reduced dimensional accuracy after processing due to the low heat resistance of the adhesive layer.

[0009] Therefore, the present inventors have investigated from a perspective completely different from that of conventional laminated films, by directly laminating a metal layer onto a polyimide film without providing an adhesive layer.

[0010] However, it has been found that simply using a polyimide film without providing an adhesive layer tends to make it difficult to achieve sufficient adhesion between the polyimide film and the metal layer.

[0011] In particular, by not providing an adhesive layer, it becomes easier to employ methods (metallizing) such as wet plating and dry plating (e.g., vacuum deposition, sputtering, and ion plating), and it becomes easier to form a metal layer with a small thickness, but on the other hand, the thinner the metal layer, the more significant the adverse effects of insufficient adhesion. Therefore, perhaps because the apparent adhesion is related to the thickness of the metal layer, it appears that the thinner the metal layer, the more a higher level of adhesion is required.

[0012] Under these circumstances, the present inventors conducted further intensive research and found that a specific polyimide film is suitable for laminating a metal layer, and that sufficient adhesion can be achieved even without providing an adhesive layer, and in particular, that even a metal layer of small thickness can be laminated with sufficient adhesion. Further research was conducted, leading to the completion of the present invention.

[0013] That is, the present invention relates to the following inventions, etc. [1] A polyimide film (especially a polyimide film for metal lamination) having a glass transition temperature (Tg) of 300°C or lower. [2] The polyimide film according to [1], having a glass transition temperature (Tg) of 180 to 290°C. [3] The polyimide film according to [1] or [2], which has a loss tangent (tan δ) at a glass transition temperature (Tg) of 0.85 or less. [4] The polyimide film according to any one of [1] to [3], wherein a ratio E'(Tg+30°C) / E'(30°C) of a storage modulus at 30°C (E'(30°C)) to a storage modulus E'(Tg+30°C) at Tg+30°C is 0.02 or more. [5] The polyimide film according to any one of [1] to [4], wherein the value of (αMD+αTD) / 2 is 20 ppm / K or less, where αMD is the linear expansion coefficient in the MD direction and αTD is the linear expansion coefficient in the TD direction. [6] The polyimide film according to any one of [1] to [5], wherein the absolute value of the difference between αMD and αTD (αMD-αTD), where αMD is the linear expansion coefficient in the MD direction and αTD is the linear expansion coefficient in the TD direction, is 10 ppm / K or less. [7] The polyimide film according to any one of [1] to [6], wherein when the film surface is thermocompression-bonded at a temperature of 400° C. and a pressure of 44 N for 1 second, the height of the irregularities generated on the film surface is 3 μm or less. [8] The glass transition temperature (Tg) is 200 to 280°C. The loss tangent (tan δ) at the glass transition temperature (Tg) is 0.75 or less, the ratio E'(Tg+30°C) / E'(30°C) of the storage modulus at 30°C (E'(30°C)) to the storage modulus E'(Tg+30°C) at Tg+30°C is 0.04 or more; When the linear expansion coefficient in the MD direction is αMD and the linear expansion coefficient in the TD direction is αTD, the value of (αMD+αTD) / 2 is 2 to 18 ppm / K, and the absolute value of the difference between αMD and αTD (αMD-αTD) is 7 ppm / K or less, When the film surface is thermocompressed at a temperature of 400°C and a pressure of 44N for 1 second, the height of the irregularities on the film surface is 2.5μm or less. Polyimide film (especially polyimide film for metal lamination). [9] The polyimide film according to any one of [1] to [8], wherein when a copper layer (e.g., a copper layer having a thickness of 8.5 μm, or a copper layer having a thickness of 8.5 μm via a metal layer (copper layer) formed by a sputtering method) is directly laminated thereon, the peel strength (e.g., 90° C. peel strength) T1 between the copper layer and the polyimide film is 0.5 kN / m or more.

[10] The polyimide film according to any one of [1] to [8], wherein T1 is the peel strength (e.g., 90°C peel strength) between a copper layer (e.g., a copper layer having a thickness of 8.5 μm, or a copper layer having a thickness of 8.5 μm via a metal layer (copper layer) formed by a sputtering method) and a polyimide film when the copper layer is directly laminated thereon, and T2 is the peel strength (e.g., 90°C peel strength) between the copper layer and the polyimide film after heating at 150°C for 168 hours, T1 is 0.5 kN / m or more, and T2 / T1 is 0.6 or more.

[11] When the thickness is 28 μm or less, the L value is 65 or more (for example, 65 to 75); When the thickness is more than 28 μm and not more than 35 μm, the L value is 60 to 70; When the thickness is more than 35 μm and not more than 40 μm, the L value is 58 to 68; When the thickness is more than 40 μm and not more than 48 μm, the L value is 56 to 66; The polyimide film according to any one of [1] to

[10] , wherein when the thickness exceeds 48 μm, the L value is 63 or less (for example, 53 to 63).

[12] The polyimide film according to any one of [1] to

[11] , wherein the polyimide constituting the polyimide film comprises, as polymerization components, an aromatic diamine component including at least one selected from 1,3-bis(3-aminophenoxy)benzene, p-phenylenediamine, and 4,4'-diaminodiphenyl ether, and an aromatic acid anhydride component including at least one selected from pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride.

[13] The polyimide film according to any one of [1] to

[12] , wherein (the polyimide constituting the polyimide film) contains at least 1,3-bis(3-aminophenoxy)benzene as a polymerization component (a diamine component containing 1,3-bis(3-aminophenoxy)benzene as a polymerization component).

[14] The polyimide film according to any one of [1] to

[13] , which contains inorganic particles.

[15] The polyimide film according to any one of [1] to

[14] , which is in a roll form.

[16] The polyimide film according to any one of [1] to

[15] , which contains inorganic particles in a proportion of 0.01 to 5 mass % and is in a roll shape having a length of 5 m or more.

[17] The polyimide film according to any one of [1] to

[16] , which is for metallizing (for plating or the like).

[18] The polyimide film according to any one of [1] to

[17] , for directly laminating a metal layer (or without an adhesive layer) (for example, directly laminating a copper layer having a thickness of 20 μm or less).

[19] A laminate film comprising a polyimide film and a metal layer laminated directly (or without an adhesive layer) on the polyimide film, the polyimide film being the polyimide film according to any one of [1] to

[18] .

[20] The laminate film according to

[19] , wherein the metal layer is a copper layer having a thickness of 20 μm or less. [twenty one] The laminate film according to

[19] or

[20] , wherein the peel strength (for example, 90° C. peel strength) T1 between the metal layer and the polyimide film is 0.5 kN / m or more. [twenty two] The laminate film according to any one of

[19] to

[21] , wherein T1 is a peel strength (e.g., 90°C peel strength) between the metal layer and the polyimide film, and T2 is a peel strength (e.g., 90°C peel strength) between the metal layer and the polyimide film after heating at 150°C for 168 hours, T1 is 0.5 kN / m or more, and T2 / T1 is 0.6 or more. Effect of the Invention

[0014] According to the present invention, a polyimide film can be provided. Such a polyimide film is suitable for use in metal lamination (for laminating metal layers, for forming metal layers) and the like.

[0015] For example, in one embodiment of the polyimide film, a metal layer (e.g., a copper layer) can be laminated (formed) with sufficient adhesion. Since such adhesion can be ensured without providing an adhesive layer (even if the metal layer is directly formed), the metal layer can also be suitably formed by metallizing (or a metallizing method or metallizing treatment, for example, a plating method (wet or dry plating method, for example, a vacuum deposition method, a sputtering method, an ion plating method)).

[0016] Therefore, such a polyimide film can achieve sufficient adhesion even with a metal layer having a small thickness (for example, a thickness of 30 μm or less, 20 μm or less, 10 μm or less, etc.).

[0017] In another embodiment of the polyimide film of the present invention, the sufficient adhesion as described above (and further the dimensional stability as described below) can be efficiently maintained even when exposed to conditions such as high temperatures.

[0018] In another embodiment of the polyimide film of the present invention, it is possible to realize a polyimide film that has a useful or effective function as a base film (substrate film) while simultaneously achieving sufficient adhesion to the metal layer as described above.

[0019] For example, in one embodiment of such another polyimide film, sufficient adhesion and heat resistance can be efficiently achieved at the same time. In another embodiment of the polyimide film, sufficient adhesion and excellent dimensional stability [e.g., dimensional stability during metal layer formation (and further, dimensional stability after metal layer formation (e.g., during processing)] can be efficiently achieved at the same time. In yet another embodiment of the polyimide film, sufficient adhesion, sufficient heat resistance, and excellent dimensional stability can be efficiently achieved at the same time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] [Polyimide film] (physical properties, etc.) A polyimide film usually has specific physical properties. Polyimide films often satisfy at least one of the following physical properties, and typically may satisfy at least the glass transition temperature (Tg) [particularly, Tg and one or more physical properties other than Tg]. The following physical properties can be efficiently satisfied by, for example, the polyimide composition, the film thickness, the film production conditions, or a combination thereof (selection and adjustment), etc.

[0021] The glass transition temperature (Tg) of the polyimide film (or the polyimide constituting the polyimide film, hereinafter the same) may be selected from a range of about 330°C or less (e.g., 320°C or less, 310°C or less) from the viewpoint of adhesion to a metal layer, etc., and may be preferably about 300°C or less (e.g., 295°C or less), more preferably 290°C or less (e.g., 285°C or less), particularly preferably about 280°C or less (e.g., 275°C or less), or may be 270°C or less (e.g., 265°C or less, 260°C or less, 255°C or less, 250°C or less).

[0022] The Tg (lower limit of Tg) of the polyimide film may be selected from a range of about 150°C or higher (e.g., 160°C or higher, 170°C or higher) from the viewpoint of heat resistance, dimensional stability, and the like (and further, a balance or compatibility with adhesion to a metal layer), and may be 180°C or higher (e.g., 190°C or higher), preferably 200°C or higher (e.g., 210°C or higher), more preferably 220°C or higher (e.g., 225°C or higher), or may be 230°C or higher (e.g., 235°C or higher, 240°C or higher, 245°C or higher, 250°C or higher, 255°C or higher, 260°C or higher, 265°C or higher, 270°C or higher), etc.

[0023] In addition, these ranges (upper and lower limits) may be appropriately combined to select a range (for example, 150 to 330° C., 180 to 300° C., etc.; the same applies to the following range descriptions).

[0024] Specific examples of Tg of the polyimide film include 150 to 300° C., preferably 180 to 290° C., and more preferably 200 to 280° C. (eg, 220 to 280° C.).

[0025] The method for measuring Tg may be a known method, and is not particularly limited. For example, the tan δ method (that is, the peak intensity of tan δ is taken as Tg) may be used. Tg may be measured, for example, by dynamic viscoelasticity measurement, such as the method described in the Examples below.

[0026] From the viewpoint of dimensional stability, heat resistance, and the like, the loss tangent (tan δ) at Tg of the polyimide film may be, for example, 1 or less (e.g., 0.9 or less), preferably 0.85 or less (e.g., 0.8 or less), more preferably 0.75 or less (e.g., 0.7 or less), particularly 0.65 or less (e.g., 0.6 or less), or may be 0.55 or less (e.g., 0.5 or less, 0.45 or less, 0.4 or less, 0.35 or less, 0.3 or less, 0.25 or less, 0.2 or less).

[0027] The lower limit of the loss tangent (tan δ) at the Tg of the polyimide film may be, for example, 0.01 or more, 0.02 or more, 0.03 or more, 0.04 or more, 0.05 or more, 0.06 or more, 0.07 or more, 0.08 or more, 0.09 or more, etc., and preferably 0.1 or more (e.g., 0.11 or more, 0.12 or more, 0.13 or more, 0.14 or more, 0.15 or more, 0.16 or more, 0.17 or more), etc.

[0028] In the polyimide film, the ratio E'(Tg+30°C) / E'(30°C) of the storage modulus at 30°C (E'(30°C)) to the storage modulus at Tg+30°C E'(Tg+30°C) may be selected from a range of about 0.01 or more (e.g., 0.015 or more) from the viewpoint of heat resistance, etc., and may be preferably 0.02 or more (e.g., more than 0.02, 0.025 or more), more preferably 0.03 or more (e.g., 0.035 or more), particularly 0.04 or more (e.g., 0.045 or more), or may be 0.05 or more (e.g., 0.055 or more, 0.06 or more, 0.065 or more, 0.07 or more, 0.075 or more, 0.08 or more).

[0029] In a polyimide film, E'(Tg+30°C) / E'(30°C) (the upper limit value) may be about 0.2 or less (e.g., 0.18 or less, 0.16 or less), preferably 0.15 or less (e.g., less than 0.15), and more preferably 0.14 or less (e.g., 0.13 or less) from the viewpoint of adhesion to a metal layer, etc. (and also a balance or compatibility with heat resistance, etc.), and can also be 0.12 or less (e.g., 0.11 or less, 0.1 or less, less than 0.1, 0.09 or less, 0.085 or less, 0.08 or less), etc.

[0030] The method for measuring the storage modulus is not particularly limited, and any known method may be used. The storage modulus may be measured, for example, by the method described in the Examples below.

[0031] In the polyimide film, the linear expansion coefficient αMD in the MD direction (the direction perpendicular to the machine conveying direction, longitudinal direction, length direction, longitudinal direction, and width direction (TD direction)) may be selected from a range of about 50 ppm / K or less (e.g., 40 ppm / K or less, 35 ppm / K or less, 30 ppm / K or less, 25 ppm / K or less), and from the viewpoint of dimensional stability (e.g., dimensional stability when a metal layer such as copper is laminated), it may be, for example, about 20 ppm / K or less (e.g., 18 ppm / K or less), preferably 16 ppm / K or less (e.g., 15 ppm / K or less), more preferably 14 ppm / K or less (e.g., 13 ppm / K or less), or may be 12 ppm / K or less (e.g., 11 ppm / K or less, 10 ppm / K or less), etc.

[0032] The lower limit of αMD (absolute value) may be 0 ppm / K, or may be more than 0 ppm / K [for example, from the viewpoint of dimensional stability (for example, dimensional stability when laminating a metal layer such as copper), 1 ppm / K or more (for example, 1.5 ppm / K or more), preferably 2 ppm / K or more (for example, 2.5 ppm / K or more), and more preferably 3 ppm / K or more (for example, 3.5 ppm / K or more)], or may be 4 ppm / K or more (for example, 4.5 ppm / K or more, 5 ppm / K or more, 5.5 ppm / K or more, 6 ppm / K or more, 6.5 ppm / K or more, 7 ppm / K or more).

[0033] A specific example of αMD may be 0 to 30 ppm / K, and from the viewpoint of dimensional stability (e.g., dimensional stability when laminating a metal layer such as copper), etc., it may be preferably 1 to 20 ppm / K (e.g., 2 to 18 ppm / K), and more preferably 3 to 17 ppm / K (e.g., 4 to 16 ppm / K, 5 to 15 ppm / K, 6 to 14 ppm / K, 6 to 12 ppm / K, 6 to 10 ppm / K), etc.

[0034] In the polyimide film, the linear expansion coefficient αTD in the TD direction (width direction, horizontal direction, transverse direction, direction perpendicular to the machine direction (MD) direction) may be selected from a range of about 50 ppm / K or less (e.g., 40 ppm / K or less, 35 ppm / K or less, 30 ppm / K or less, 25 ppm / K or less), and from the viewpoint of dimensional stability (e.g., dimensional stability when laminating a metal layer such as copper), it may be, for example, about 20 ppm / K or less (e.g., 18 ppm / K or less), preferably 16 ppm / K or less (e.g., 15 ppm / K or less), more preferably 14 ppm / K or less (e.g., 13 ppm / K or less), or may be 12 ppm / K or less (e.g., 11 ppm / K or less, 10 ppm / K or less), etc.

[0035] The lower limit of αTD may be 0 ppm / K, or may be more than 0 ppm / K [for example, 1 ppm / K or more (for example, 1.5 ppm / K or more), preferably 2 ppm / K or more (for example, 2.5 ppm / K or more), and more preferably 3 ppm / K or more (for example, 3.5 ppm / K or more)], or may be 4 ppm / K or more (for example, 4.5 ppm / K or more, 5 ppm / K or more, 5.5 ppm / K or more, 6 ppm / K or more, 6.5 ppm / K or more, 7 ppm / K or more).

[0036] A specific example of αTD may be 0 to 30 ppm / K, and from the viewpoint of dimensional stability (e.g., dimensional stability when laminating a metal layer such as copper), etc., it may be preferably 1 to 20 ppm / K (e.g., 2 to 18 ppm / K), and more preferably 3 to 17 ppm / K (e.g., 4 to 16 ppm / K, 5 to 15 ppm / K, 6 to 14 ppm / K, 6 to 12 ppm / K, 6 to 10 ppm / K), etc.

[0037] In the polyimide film, the value of (αMD+αTD) / 2 may be selected from a range of about 50 ppm / K or less (e.g., 40 ppm / K or less, 35 ppm / K or less, 30 ppm / K or less, 25 ppm / K or less), and from the viewpoint of dimensional stability (e.g., dimensional stability when laminating a metal layer such as copper), it may be, for example, about 20 ppm / K or less (e.g., 18 ppm / K or less), preferably 16 ppm / K or less (e.g., 15 ppm / K or less), more preferably 14 ppm / K or less (e.g., 13 ppm / K or less), or may be 12 ppm / K or less (e.g., 11 ppm / K or less, 10 ppm / K or less), etc.

[0038] The lower limit of (αMD+αTD) / 2 may be 0 ppm / K, or may be more than 0 ppm / K [for example, from the viewpoint of dimensional stability (for example, dimensional stability when laminating a metal layer such as copper), 1 ppm / K or more (for example, 1.5 ppm / K or more), preferably 2 ppm / K or more (for example, 2.5 ppm / K or more), and more preferably 3 ppm / K or more (for example, 3.5 ppm / K or more)], or may be 4 ppm / K or more (for example, 4.5 ppm / K or more, 5 ppm / K or more, 5.5 ppm / K or more, 6 ppm / K or more, 6.5 ppm / K or more, 7 ppm / K or more).

[0039] A specific example of (αMD+αTD) / 2 may be, for example, 0 to 30 ppm / K, and from the viewpoint of dimensional stability (e.g., dimensional stability when laminating a metal layer such as copper), etc., it may be preferably 1 to 20 ppm / K (e.g., 2 to 18 ppm / K), and more preferably 3 to 17 ppm / K (e.g., 4 to 16 ppm / K, 5 to 15 ppm / K, 6 to 14 ppm / K, 6 to 12 ppm / K, 6 to 10 ppm / K), etc.

[0040] In a polyimide film, the absolute value of the difference between αMD and αTD (αMD-αTD) may be selected from a range of about 30 ppm / K or less (e.g., 25 ppm / K or less, 20 ppm / K or less), and from the viewpoint of dimensional stability (e.g., dimensional stability when laminating a metal layer such as copper), it may be, for example, 15 ppm / K or less (e.g., 12 ppm / K or less), preferably 10 ppm / K or less (e.g., 8 ppm / K or less), more preferably 7 ppm / K or less (e.g., 6 ppm / K or less), or may be 5 ppm / K or less (e.g., 4.5 ppm / K or less, 4 ppm / K or less, 3.5 ppm / K or less, 3 ppm / K or less, 2.5 ppm / K or less, 2 ppm / K or less, 1.5 ppm / K or less, 1 ppm / K or less), etc.

[0041] The absolute value (lower limit value) of the difference between αMD and αTD (αMD-αTD) may be 0 ppm / K or may be greater than 0 ppm / K (for example, 0.1 ppm / K or more, 0.2 ppm / K or more, 0.3 ppm / K or more, 0.4 ppm / K or more, 0.5 ppm / K or more).

[0042] Incidentally, αMD and αTD are not particularly limited, but may be measured in a specific temperature range (for example, 50 to 200°C) or may be measured under specific conditions (for example, a temperature rise rate of 10°C / min). Specifically, they may be measured by the method of the examples described later.

[0043] The polyimide film may have a relatively large L value from the viewpoint of visibility, etc. For example, the L value of the polyimide film may be, depending on the thickness, etc., for example, 50 or more (e.g., 51 or more), preferably 52 or more (e.g., 53 or more), more preferably 54 or more (e.g., 55 or more), or may be 56 or more (e.g., 57 or more, 58 or more, 59 or more, 60 or more, 61 or more, 62 or more, 63 or more, 64 or more, 65 or more, or 66 or more).

[0044] The L value may be related to the adhesion with the metal layer. For example, although the L value depends on the combination with the polyimide composition and other physical properties, by selecting an appropriate L value, the adhesion with the metal layer [specifically, the index corresponding to T1 (and further T2, T2 / T1) described later] may be improved or enhanced. The L value is related to the strength (crosslinking) and the degree of deterioration of the film surface, which is considered to affect the adhesion. In other words, by selecting an appropriate range of L values ​​(for example, a specific range of L values ​​according to the thickness of the film), it is considered that the improvement of the strength (crosslinking) and the suppression of deterioration on the film surface can be achieved in a well-balanced manner, and excellent adhesion can be realized. In such a case, since the L value may decrease as the thickness of the polyimide film increases, the range of the L value may be set according to the thickness. For example, when the thickness is 28 μm or less (e.g., 24 to 27 μm), the L value may be about 65 or more (e.g., 65 to 75, preferably 67 to 73); when the thickness is more than 28 μm and less than 35 μm (e.g., 29 to 32 μm), the L value may be about 60 to 70 (e.g., 62 to 68); when the thickness is more than 35 μm and less than 40 μm (e.g., 36 to 39 μm), the L value may be about 58 to 68 (e.g., 60 to 66); when the thickness is more than 40 μm and less than 48 μm (e.g., 41 to 44 μm), the L value may be about 56 to 66 (e.g., 58 to 64); and when the thickness is more than 48 μm (e.g., 49 to 52 μm), the L value may be about 63 or less [e.g., 53 to 63, preferably 61 or less (e.g., 55 to 61)].

[0045] The L value is defined, for example, in the formula difference display method of JIS Z 8730. Specifically, it has Lab coordinate system by Hunter formula difference, and it is also possible to calculate the L value from the tristimulus values ​​X, Y, and Z defined in JIS Z 8722 by the following formula. L value = 10Y 1 / 2 a=17.5(1.02XY) / Y 1 / 2 b=7.0(Y-0.847Z) / Y 1 / 2 (a, b = chromaticity index in Hunter's color difference formula, X, Y, Z = tristimulus value in XYZ system)

[0046] Specifically, the L value may be measured by the method described in the Examples below. The L value can be efficiently adjusted by, for example, the film production conditions, and is particularly easily adjusted (easily influenced) by the heat treatment conditions [particularly the maximum heating temperature (and further the duration)].

[0047] The polyimide film may be a polyimide film in which, when the film surface is thermocompressed (pressed) at a temperature of 400°C and a pressure of 44 N for 1 second, the height of the unevenness generated on the film surface is about 5 μm or less, preferably 4 μm or less (e.g., 3.5 μm or less), more preferably 3 μm or less (e.g., 2.8 μm or less), and particularly 2.5 μm or less (e.g., 2.4 μm or less, 2.3 μm or less, 2.2 μm or less, 2.1 μm or less, 2 μm or less, 1.9 μm or less).

[0048] The polyimide film may be a polyimide film in which, when the film surface is thermocompression-bonded at a temperature of 400° C. and a pressure of 44 N for 1 second, the height (lower limit) of the unevenness generated on the film surface is 0 μm or more, and from the viewpoint of balance with adhesion, etc., the height is more than 0 μm (for example, 0.1 μm or more, 0.2 μm or more, 0.3 μm or more, 0.4 μm or more, 0.5 μm or more, 0.6 μm or more, 0.7 μm or more, 0.8 μm or more, 0.9 μm or more, 1 μm or more, 1.1 μm or more, 1.2 μm or more, 1.3 μm or more, 1.4 μm or more, 1.5 μm or more, 1.6 μm or more, 1.7 μm or more, 1.8 μm or more, 1.9 μm or more, 2 μm or more).

[0049] The polyimide film of the present invention can achieve both sufficient adhesion to a metal layer and excellent heat resistance (thermocompression bonding property) as described above.

[0050] Specifically, the height of the unevenness as described above may be measured by the method described in the Examples below.

[0051] The polyimide film can achieve sufficient adhesion with the metal layer. For example, when the metal layer is directly laminated (on the polyimide film) (lamination without an adhesive layer), the peel strength (adhesion, peel strength, 90°C peel strength) between the metal layer and the polyimide film (T1) is more than 0.4 kN / m (e.g., 0.45 kN / m or more), preferably 0.5 kN / m or more (e.g., 0.55 kN / m or more), more preferably 0.6 kN / m or more (e.g., 0.65 kN / m or more), particularly 0.7 kN / m or more (e.g., 0.75 kN / m or more), particularly preferably 0.8 kN / m or more (e.g., more than 0.8 kN / m, 0.85 kN / m or more, 0.9 kN / m or more).

[0052] The upper limit of T1 is not particularly limited, but may be, for example, 5 kN / m or less, 4 kN / m or less, 3 kN / m or less, 2.5 kN / m or less, 2 kN / m or less, 1.5 kN / m or less, 1.2 kN / m or less, 1 kN / m or less, etc.

[0053] Such adhesion can be maintained at a relatively high level even under conditions such as high temperatures (e.g., severe conditions). Examples of such polyimide films include polyimide films in which, when the peel strength (adhesion, peel strength) between a metal layer and a polyimide film when the metal layer is directly laminated (on a polyimide film) (lamination without an adhesive layer) is T1, and the peel strength (adhesion, peel strength) between the metal layer and the polyimide film after heating at 150°C for 168 hours is T2, T2 / T1 is 0.3 or more (e.g., 0.4 or more), preferably 0.5 or more (e.g., more than 0.5, 0.55 or more), more preferably 0.6 or more (e.g., 0.65 or more), particularly 0.7 or more (e.g., 0.72 or more), and particularly preferably 0.75 or more (e.g., more than 0.75, 0.78 or more, 0.8 or more).

[0054] The upper limit of T2 / T1 may be 1, or may be less than 1 (for example, 0.99 or less, 0 0.98 or less, 0.97 or less, 0.96 or less, 0.95 or less, 0.94 or less, 0.93 or less, 0.92 or less, 0.91 or less, 0.9 or less).

[0055] The value of T2 may be, for example, greater than 0.3 kN / m (e.g., 0.35 kN / m or more), preferably 0.4 kN / m or more (e.g., 0.45 kN / m or more), more preferably 0.5 kN / m or more (e.g., 0.55 kN / m or more), particularly 0.6 kN / m or more (e.g., 0.65 kN / m or more), and particularly preferably 0.7 kN / m or more (e.g., greater than 0.7 kN / m, 0.75 kN / m or more, 0.8 kN / m or more).

[0056] The upper limit of T2 is not particularly limited, but may be, for example, 5 kN / m or less, 4 kN / m or less, 3 kN / m or less, 2.5 kN / m or less, 2 kN / m or less, 1.5 kN / m or less, 1.2 kN / m or less, 1 kN / m or less, 0.9 kN / m or less, 0.8 kN / m or less, etc.

[0057] In the measurement of T1 (and further T2), the metal layer is not particularly limited, and may be a specific metal layer {for example, one corresponding to the examples described later, that is, a copper layer having a thickness of 8.5 μm [for example, a 25 nm-thick nickel / chromium alloy (nickel / chromium=80 / 20) layer (for example, a layer formed by sputtering) and a 100 nm-thick copper layer (for example, a layer formed by sputtering) formed on the nickel / chromium alloy layer, and a copper layer having a thickness of 8.5 μm (for example, a layer formed by plating)].

[0058] The method for measuring T1 (and further T2) may be, for example, a method conforming to Method A in the copper foil peel strength test method described in JIS C 6471 (for example, a pulling angle of 90° and a pulling speed of 50 mm / min). More specifically, T1 (and further T2) may be measured by the method described in the Examples below.

[0059] The thickness of the polyimide film can be appropriately selected depending on the application, etc., but from the viewpoint of suitable use (functioning) as a substrate (base film) of a laminate film, for example, it may be 1 μm or more (e.g., 2 μm or more), preferably 3 μm or more (e.g., 4 μm or more), more preferably 5 μm or more (e.g., 6 μm or more), etc., and may be about 7 μm or more (e.g., 8 μm or more, 10 μm or more, 12 μm or more, 15 μm or more, 18 μm or more, 20 μm or more, 22 μm or more, 25 μm or more, 28 μm or more, 30 μm or more, 32 μm or more, 35 μm or more).

[0060] The thickness (upper limit) of such a polyimide film is not limited, but may be, for example, 300 μm or less (e.g., 250 μm or less), preferably 200 μm or less (e.g., 150 μm or less), and more preferably about 100 μm or less (e.g., 80 μm or less), or may be 70 μm or less (e.g., 60 μm or less, 55 μm or less, 50 μm or less, 45 μm or less, 40 μm or less, 35 μm or less, 30 μm or less).

[0061] Specific examples of the thickness of the polyimide film include 1 to 200 μm, preferably 3 to 100 μm, and more preferably 5 to 80 μm.

[0062] The polyimide film may be a laminate of a plurality of polyimide films, but typically may be a single polyimide film.

[0063] The polyimide film may be an unstretched film or a stretched film (uniaxially or biaxially stretched film). In such a stretched film, the stretching conditions (e.g., the stretch ratio in the TD direction and / or the MD direction, etc.) may be the conditions described later.

[0064] In the present invention, sufficient adhesion and the like can be easily and efficiently achieved even in the case of a stretched film.

[0065] (Composition, manufacturing method, etc.) A polyimide film (or a polyimide or polyamic acid constituting the polyimide film) usually contains an aromatic diamine component and an aromatic acid anhydride component as raw materials (polymerization components).

[0066] Examples of the aromatic diamine component include paraphenylenediamine, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, metaphenylenediamine, diaminodiphenylpropane (e.g., 4,4'-diaminodiphenylpropane, 3,4'-diaminodiphenylpropane, 3,3'-diaminodiphenylpropane, etc.), diamino Diphenylmethane (e.g., 4,4'-diaminodiphenylmethane, 3,4'-diaminodiphenylmethane, 3,3'-diaminodiphenylmethane, etc.), benzidine, diaminodiphenyl sulfide (e.g., 4,4'-diaminodiphenyl sulfide, 3,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfide, etc.), diaminodiphenyl sulfone (e.g., 4,4'-diaminodiphenyl sulfone, 3,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, etc.), 2 ,6-Diaminopyridine, bis-(4-aminophenyl)diethylsilane, 3,3'-dichlorobenzidine, bis-(4-aminophenyl)ethylphosphinoxide, bis-(4-aminophenyl)phenylphosphinoxide, bis-(4-aminophenyl)-N-phenylamine, bis-(4-aminophenyl)-N-methylamine, 1,5-diaminonaphthalene, 3,3'-dimethyl-4,4'-diaminobiphenyl, 3,4'-dimethyl-3',4-diaminobiphenyl, 3,3'-dimethoxybenzidine, 2,4-biphenyl Examples of such compounds include bis(p-β-amino-t-butylphenyl)ether, bis(p-β-amino-t-butylphenyl)ether, p-bis(2-methyl-4-aminopentyl)benzene, p-bis-(1,1-dimethyl-5-aminopentyl)benzene, m-xylylenediamine, p-xylylenediamine, 2,5-diamino-1,3,4-oxadiazole, 2,2-bis(4-aminophenyl)hexafluoropropane, N-(3-aminophenyl)-4-aminobenzamide, and 4-aminophenyl-3-aminobenzoate. These compounds can be used alone or in combination of two or more.

[0067] From the viewpoint of easily and efficiently achieving the above-mentioned physical properties, the aromatic diamine component may preferably contain at least one selected from 1,3-bis(3-aminophenoxy)benzene, paraphenylenediamine, and 4,4'-diaminodiphenyl ether, and more preferably may contain at least one selected from 1,3-bis(3-aminophenoxy)benzene and paraphenylenediamine. In particular, from the viewpoints of adhesion to the metal layer, heat resistance, dimensional stability, and the like, the aromatic diamine component may contain at least 1,3-bis(3-aminophenoxy)benzene.

[0068] When the aromatic diamine component contains at least one selected from 1,3-bis(3-aminophenoxy)benzene, paraphenylenediamine, and 4,4'-diaminodiphenyl ether, the ratio of the one selected from 1,3-bis(3-aminophenoxy)benzene, paraphenylenediamine, and 4,4'-diaminodiphenyl ether to the entire aromatic diamine component (or all diamine components) may be selected from a range of about 30 mol% or more (e.g., 40 to 100 mol%), for example, 50 mol% or more (e.g., 60 mol% or more), preferably 70 mol% or more (e.g., 80 mol% or more), and more preferably 90 mol% or more (e.g., 95 mol% or more, 97 mol% or more, 98 mol% or more, 99 mol% or more, 100 mol%).

[0069] When the aromatic diamine component contains at least one selected from 1,3-bis(3-aminophenoxy)benzene and paraphenylenediamine, the ratio of the at least one selected from 1,3-bis(3-aminophenoxy)benzene and paraphenylenediamine to the entire aromatic diamine component (or all diamine components) may be selected from a range of about 30 mol% or more (e.g., 40 to 100 mol%), for example, 50 mol% or more (e.g., 60 mol% or more), preferably 70 mol% or more (e.g., 80 mol% or more), and more preferably 90 mol% or more (e.g., 95 mol% or more, 97 mol% or more, 98 mol% or more, 99 mol% or more, 100 mol%).

[0070] When the aromatic diamine component contains 1,3-bis(3-aminophenoxy)benzene, the proportion of 1,3-bis(3-aminophenoxy)benzene to the entire aromatic diamine component (or all diamine components) may be selected from a range of about 20 mol% or more (e.g., 25 to 100 mol%, 25 to 90 mol%, 25 to 80 mol%, etc.), for example, 30 mol% or more (e.g., 30 to 75 mol%, 35 mol% or more, 35 to 65 mol%), preferably 40 mol% or more (e.g., 40 to 65 mol%, 45 mol% or more), and more preferably 50 mol% or more (e.g., 55 mol% or more, 55 to 75 mol%, 56 to 72 mol%, 58 to 70 mol%, 60 mol% or more).

[0071] When the aromatic diamine component contains paraphenylenediamine, the proportion of paraphenylenediamine to the entire aromatic diamine component (or all diamine components) may be selected from a range of about 1 mol% or more (e.g., 1 to 100 mol%, 2 to 90 mol%, 3 to 80 mol%, etc.), for example, 5 mol% or more (e.g., 5 to 70 mol%, 10 mol% or more, 10 to 65 mol%), preferably 15 mol% or more (e.g., 15 to 65 mol%, 15 to 55 mol%, 15 to 50 mol%), and more preferably 20 mol% or more (e.g., 20 to 65 mol%, 25 mol% or more, 25 to 60 mol%, 25 to 45 mol%, 28 to 44 mol%, 30 mol% or more, 30 to 55 mol%, 30 to 42 mol%).

[0072] When the aromatic diamine component contains paraphenylenediamine and 1,3-bis(3-aminophenoxy)benzene, the molar ratio of paraphenylenediamine to 1,3-bis(3-aminophenoxy)benzene may be, for example, about 10 / 90 to 70 / 30 (e.g., 15 / 85 to 65 / 35), preferably about 20 / 80 to 60 / 40 (e.g., 25 / 75 to 55 / 45, 25 / 75 to 50 / 50, 30 / 70 to 50 / 50, 35 / 65 to 45 / 55).

[0073] Examples of aromatic acid anhydride components (aromatic tetracarboxylic acid components) include pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,3,6,7-naphthalenedicarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)ether, Pyridine-2,3,5,6-tetracarboxylic dianhydride, naphthalene tetracarboxylic dianhydride (e.g., 1,2,4,5-naphthalene tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 1,4,5,8-decahydronaphthalene tetracarboxylic dianhydride, 4,8-dimethyl-1,2,5,6-hexahydronaphthalene tetracarboxylic dianhydride, 2,6-dichloro-1,4,5,8-naphthalene tetracarboxylic dianhydride, 2,7-dichloro-1,4,5,8-naphthalenetetracarboxylic dianhydride, 2,3,6,7-tetrachloro-1,4,5,8-naphthalenetetracarboxylic dianhydride, 1,8,9,10-phenanthrenetetracarboxylic dianhydride, 2,2-bis(2,3-dicarboxyphenyl)propane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride Examples of suitable dianhydrides include benzene-1,2,3,4-tetracarboxylic dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, benzene-1,2,3,4-tetracarboxylic dianhydride, 3,4,3',4'-benzophenonetetracarboxylic dianhydride, etc., and preferably, pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, etc. These can be used alone or in combination of two or more.

[0074] From the viewpoint of easily and efficiently achieving the above-mentioned physical properties in combination with the aromatic diamine component, the aromatic acid anhydride component preferably contains at least one selected from pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride, and more preferably contains pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride.

[0075] When the aromatic acid anhydride component contains at least one selected from pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride, the ratio of at least one selected from pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride to the entire aromatic acid anhydride component (or all acid anhydride components) may be selected from a range of about 30 mol% or more (e.g., 40 to 100 mol%), for example, 50 mol% or more (e.g., 60 mol% or more), preferably 70 mol% or more (e.g., 80 mol% or more), more preferably 90 mol% or more (e.g., 95 mol% or more, 97 mol% or more, 98 mol% or more, 99 mol% or more, 100 mol%).

[0076] When the aromatic acid anhydride component contains pyromellitic dianhydride, the ratio of pyromellitic dianhydride to the entire aromatic acid anhydride component (or total acid anhydride component) may be selected from a range of about 1 mol% or more (e.g., 1 to 100 mol%, 2 to 90 mol%, 3 to 80 mol%, 5 mol% or more, etc.), for example, 10 mol% or more (e.g., 15 to 75 mol%, 15 mol% or more, 15 to 70 mol%), preferably 20 mol% or more (e.g., 20 to 70 mol%, 20 to 60 mol%, 20 to 55 mol%), more preferably 25 mol% or more (e.g., 25 to 70 mol%, 25 to 65 mol%, 30 mol% or more, 30 to 65 mol%, 30 to 60 mol%, 35 mol% or more, 35 to 60 mol%, 35 to 55 mol%, 40 to 50 mol%).

[0077] When the aromatic acid anhydride component contains 3,3',4,4'-biphenyltetracarboxylic dianhydride, the proportion of 3,3',4,4'-biphenyltetracarboxylic dianhydride relative to the entire aromatic acid anhydride component (or all acid anhydride components) may be selected from a range of about 5 mol% or more (e.g., 10 mol% or more, 15 mol% or more, 20 to 100 mol%, 20 to 85 mol%, 20 to 75 mol%, etc.), for example, 25 mol% or more (e.g., 25 to 70 mol%, 30 mol% or more, 30 to 60 mol%), preferably 35 mol% or more (e.g., 35 to 75 mol%, 35 to 60 mol%, 40 mol% or more, 40 to 70 mol%), and more preferably 45 mol% or more (e.g., 45 to 65 mol%, 50 mol% or more, 55 mol% or more).

[0078] When the aromatic acid anhydride component contains pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride, the molar ratio of pyromellitic dianhydride to 3,3',4,4'-biphenyltetracarboxylic dianhydride may be, for example, about 15 / 85 to 75 / 25 (e.g., 20 / 80 to 70 / 30), preferably about 25 / 75 to 65 / 35 (e.g., 30 / 70 to 60 / 40, 30 / 70 to 55 / 45, 35 / 65 to 55 / 45, 40 / 60 to 50 / 50).

[0079] The raw material components of the polyimide film (polymerization components, diamine components, and acid anhydride components) may contain other polymerization components (e.g., other acid anhydride components, other diamine components) other than the above-mentioned aromatic acid anhydride components and aromatic diamine components, as long as the effects of the present invention are not impaired. Examples of other diamine components (non-aromatic diamine components) include diaminoadamantanes (e.g., 1,3-diaminoadamantane, 3,3'-diamino-1,1'-diaminoadamantane, 3,3'-diaminomethyl-1,1'-diadamantane, etc.), diaminoalkanes (e.g., hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, 3-methylheptamethylenediamine, 4,4'-dimethylheptamethylenediamine, 2,11-diaminododecane, 2,2-dimethylpropane, etc.), Examples of the dimethylaminophenyl ester include propylenediamine, 3-methoxyhexaethylenediamine, 2,5-dimethylhexamethylenediamine, 2,5-dimethylheptamethylenediamine, 5-methylnonamethylenediamine, 1,4-diaminocyclohexane, 1,12-diaminooctadecane, 1,2-bis(3-aminopropoxy)ethane, 2,5-diamino-1,3,4-oxadiazole, 2,2-bis(4-aminophenyl)hexafluoropropane, N-(3-aminophenyl)-4-aminobenzamide, 4-aminophenyl-3-aminobenzoate, etc. These can be used alone or in combination of two or more.

[0080] In addition, when the polymerization components contain other polymerization components (other diamine components, etc.), the ratio of the other polymerization components to the total polymerization components may be a small ratio, for example, 20 mol% or less (for example, 15 mol% or less, 10 mol% or less, 5 mol% or less, 3 mol% or less, 1 mol% or less).

[0081] The polyimide film may contain other components besides polyimide (resin component). For example, the polyimide film may contain inorganic particles from the viewpoint of handling (easy lubricity) etc. The other components may be contained in one or more kinds.

[0082] When inorganic particles are contained, the inorganic particles are usually dispersed in the polyimide film. Examples of inorganic particles include oxides {e.g., SiO2 (silica), TiO2 (titanium oxide (IV)), etc.}, inorganic acid salts {e.g., phosphate (hydrogen) salts such as CaHPO4 (calcium hydrogen phosphate), CaPO4 (calcium phosphate), Ca2P2O7 (calcium diphosphate), etc., and carbonates such as CaCO3 (calcium carbonate)}. The inorganic particles may be used alone or in combination of two or more kinds.

[0083] The average particle size of the inorganic particles to be dispersed may be, for example, about 0.3 to 3.5 μm (e.g., 0.5 to 3 μm), preferably about 0.5 to 2.5 μm (e.g., 0.5 to 2.2 μm), or may be 0.5 to 2.0 μm (e.g., 0.5 to 1.9 μm), 1 to 3.5 μm (e.g., 1.5 to 3.0 μm, 2.0 to 2.5 μm), etc. The method for measuring the average particle size of the inorganic particles is not particularly limited, and any known method may be used.

[0084] The particle size distribution of inorganic particles (inorganic particles to be dispersed) is preferably narrow, that is, the proportion of inorganic particles of similar size to the total inorganic particles is preferably high. Specifically, it is preferable that inorganic particles of a specific particle size (e.g., 0.5 to 2.5 μm, 1 to 3.5 μm, etc.) account for 80 volume % or more (e.g., 80 to 100 volume %) of the total inorganic particles.

[0085] When inorganic particles are contained, the proportion of the inorganic particles in the polyimide film may be, for example, 0.01 mass % or more (e.g., 0.02 mass % or more), preferably 0.03 mass % or more (e.g., 0.04 mass % or more), and more preferably 0.05 mass % or more.

[0086] The upper limit of the proportion of inorganic particles in the polyimide film may be selected from a range of about 5 mass% or less (e.g., 3 mass% or less, 2 mass% or less, 1.5 mass% or less), and may be 1 mass% or less (e.g., 0.9 mass% or less), preferably 0.8 mass% or less (e.g., 0.7 mass% or less), and more preferably 0.6 mass% or less (e.g., 0.55 mass% or less, 0.5 mass% or less, 0.45 mass% or less, 0.4 mass% or less, 0.3 mass% or less), etc.

[0087] The polyimide film may be in a laminated state, and in particular in a wound state, ie, in a roll form (roll). The width of the polyimide film (e.g., a roll-shaped polyimide film) is not particularly limited, and may be, for example, 30 mm or more, 45 mm or more, 50 mm or more, 75 mm or more, 100 mm or more, 150 mm or more, 200 mm or more, 300 mm or more, 500 mm or more, etc., or may be 3000 mm or less, 2000 mm or less, 1000 mm or less, etc. The polyimide film may have a relatively large size. The length of such a polyimide film (for example, a roll-shaped polyimide film) may be, for example, 1 m or more (for example, 5 m or more), 10 m or more (for example, 20 m or more), preferably 30 m or more (for example, 40 m or more), more preferably 50 m or more (for example, 100 m or more), and may be 200 m or more, 300 m or more, 500 m or more, 1000 m or more, 2000 m or more, 3000 m or more, 5000 m or more, etc.

[0088] The polyimide film may be surface-treated (for example, by electrical treatment such as corona treatment or plasma treatment, or by blasting). Such surface treatment may be performed on one or both sides. Depending on the surface treatment (plasma treatment, etc.) and the extent of the treatment, it may be a factor in reducing adhesion (for example, the value embodied in the aforementioned T2 or T2 / T1) when exposed to conditions such as high temperature. On the other hand, in the present invention, sufficient adhesion can be achieved without surface treatment. Therefore, the polyimide film may be plasma-treated, but it is also preferable to select one that is not plasma-treated or that is only slightly plasma-treated.

[0089] The method for producing the polyimide film is not particularly limited, but a representative method will be described below. In obtaining a polyimide film, first, polymerization components (components containing an aromatic diamine component and an aromatic acid anhydride component) are polymerized in an organic solvent to obtain a polyamic acid solution (hereinafter also referred to as a polyamic acid solution).

[0090] Specific examples of organic solvents used to form the polyamic acid solution include sulfoxide-based solvents such as dimethyl sulfoxide and diethyl sulfoxide, formamide-based solvents such as N,N-dimethylformamide and N,N-diethylformamide, acetamide-based solvents such as N,N-dimethylacetamide and N,N-diethylacetamide, pyrrolidone-based solvents such as N-methyl-2-pyrrolidone and N-vinyl-2-pyrrolidone, phenol-based solvents such as phenol, o-, m-, or p-cresol, xylenol, halogenated phenols, and catechol, and aprotic polar solvents such as hexamethylphosphoramide and γ-butyrolactone. These may be used alone or in combination of two or more. Furthermore, they may be used in combination with aromatic hydrocarbons such as xylene and toluene.

[0091] The polymerization method of the polyamic acid solution may be any known method, for example, (1) A method in which the entire amount of the diamine component (aromatic diamine component) is first placed in a solvent, and then an acid anhydride component (aromatic acid anhydride component) is added in an amount equivalent to the total amount of the diamine component (aromatic diamine component) to polymerize the mixture. (2) A method in which the entire amount of the acid anhydride component (aromatic acid anhydride component) is first placed in a solvent, and then the diamine component (aromatic diamine component) is added in an amount equivalent to the acid anhydride component (aromatic acid anhydride component) to polymerize the mixture. (3) A method of polymerizing by adding one diamine component (aromatic diamine component) to a solvent, mixing one acid anhydride component (aromatic acid anhydride component) in a ratio of 95 to 105 mol % relative to the reactants for a time required for reaction, adding the other aromatic diamine component, and then adding the other acid anhydride component (aromatic acid anhydride component) so that the total diamine component (aromatic diamine component) and the total acid anhydride components (aromatic acid anhydride components) are approximately equivalent in weight, (4) A method of polymerizing by adding one acid anhydride component (aromatic acid anhydride component) to a solvent, mixing one diamine component (aromatic diamine component) in a ratio of 95 to 105 mol % relative to the reactive components for a time required for reaction, adding the other acid anhydride component (aromatic acid anhydride component), and then adding the other diamine component (aromatic diamine component) so that the total diamine components (aromatic diamine components) and the total acid anhydride components (aromatic acid anhydride components) are approximately equivalent in weight, (5) In a solvent, one diamine component (aromatic diamine component) is reacted with an acid anhydride component (aromatic acid anhydride component) so that one is in excess to prepare a polyamic acid solution (A), and in a different solvent, the other diamine component (aromatic diamine component) is reacted with an acid anhydride component (aromatic acid anhydride component) so that one is in excess to prepare a polyamic acid solution (B).The polyamic acid solutions (A) and (B) thus obtained are then mixed to complete the polymerization. In this case, when preparing the polyamic acid solution (A), if the diamine component (aromatic diamine component) is in excess, the acid anhydride component (aromatic acid anhydride component) is added in excess in the polyamic acid solution (B); conversely, when the acid anhydride component (aromatic acid anhydride component) is in excess in the polyamic acid solution (A), the diamine component (aromatic diamine component) is added in excess in the polyamic acid solution (B); the polyamic acid solutions (A) and (B) are mixed together, and adjustments are made so that the total diamine components (aromatic diamine components) and total acid anhydride components (aromatic acid anhydride components) used in these reactions are approximately equivalent. The polymerization method is not limited to these, and other known methods may be used.

[0092] The acid anhydride component (aromatic acid anhydride component) and the diamine component (aromatic diamine component) constituting the polyamic acid are polymerized in a ratio in which the number of moles of each is approximately equal, but one of them may be blended in excess of the other within a range of 10 mol %, preferably 5 mol %.

[0093] The polymerization reaction is preferably carried out in an organic solvent while stirring. The polymerization temperature is not particularly limited, but is usually carried out at an internal temperature of 0 to 80°C of the reaction solution. The polymerization time is not particularly limited, but is preferably carried out continuously for 10 minutes to 30 hours. The polymerization reaction may be divided or the temperature may be increased or decreased as necessary. There is no particular restriction on the order of addition of both reactants, but it is preferable to add the aromatic acid anhydride to the solution of the aromatic diamine component. Vacuum degassing during the polymerization reaction is an effective method for producing a high-quality organic solvent solution of polyamic acid. The polymerization reaction may be controlled by adding a small amount of a terminal blocking agent to the aromatic diamines before the polymerization reaction. The terminal blocking agent is not particularly limited, and a known agent can be used.

[0094] The polyamic acid solution thus obtained may contain a solid content of usually 5 to 40% by weight, preferably 10 to 30% by weight. The viscosity is not particularly limited, but is usually 10 to 2000 Pa·s as measured by a Brookfield viscometer, and is preferably 100 to 1000 Pa·s for stable liquid transfer. The polyamic acid in the organic solvent solution may be partially imidized.

[0095] When obtaining a polyimide film containing inorganic particles, the inorganic particles may be contained in a polyamic acid solution. When obtaining a polyamic acid solution containing inorganic particles, the inorganic particles may be added to a polyamic acid solution that has been polymerized in advance, or the polyamic acid solution may be polymerized in the presence of the inorganic particles.

[0096] It is preferable to use the inorganic particles as a slurry (inorganic particle slurry) dispersed in a solvent (e.g., a polar solvent such as N,N-dimethylformamide, N,N-dimethylacetamide, dimethylsulfoxide, or N-methylpyrrolidone) because this can prevent aggregation.

[0097] The method for producing the inorganic particle slurry is not particularly limited, and may be a conventionally known method. For example, the method for producing the inorganic particle slurry may be a method of mixing inorganic particles and a solvent using a mixer. As the mixer, it is preferable to use a mixer with high shear force such as a high-speed disperser, a homomixer, a ball mill, a coalesce mixer, or a stirring disperser. In addition, a wet grinding process may be performed to reduce the average particle size. For example, a bead mill, a sand mill, or the like may be used for the wet grinding process.

[0098] The inorganic particle slurry may be a commercially available product in which inorganic particles are dispersed in a solvent in advance. The inorganic particle slurry may contain other organic solvents, compounding agents, and the like, as necessary.

[0099] The concentration of the inorganic particles in the inorganic particle slurry is not particularly limited, but is, for example, 1 to 80% by weight, preferably 1 to 60% by weight, and more preferably 1 to 40% by weight.

[0100] In addition, it is preferable to filter the inorganic particle slurry through a filter having a predetermined pore size (for example, a cut filter having a pore size of 15 μm or less, preferably a pore size of 13 μm or less, more preferably a pore size of 11 μm or less, even more preferably a pore size of 5 μm or less, and particularly preferably a pore size of 3 μm or less) from the viewpoints of suppressing aggregation of inorganic particles and removing inorganic particles of a predetermined particle size (for example, inorganic particles of 15 μm or more) in the polyimide film.

[0101] The material of the filter is not particularly limited, and examples thereof include polymer materials (eg, polyethylene, polypropylene, polytetrafluoroethylene, etc.) and metals (eg, stainless steel, etc.).

[0102] The amount of inorganic particles added may be appropriately selected according to the desired content in the polyimide film (for example, 0.03 to 0.8 parts by mass per 100 parts by mass of polyimide when the polyimide is formed).

[0103] Next, a method for producing a polyimide film will be described. The polyimide film can be produced (produced) through, for example, a step (1) of cyclizing a polyamic acid solution to obtain a gel film (converting a polyamic acid or a polyamic acid solution into a gel film), a step (2) of drying (and removing the solvent) the obtained gel film, and a step (3) of heat treatment. The drying and heat treatment promote drying and imidization.

[0104] In step (1), the method for cyclizing the polyamic acid solution is not particularly limited, but specific examples include (i) a method in which the polyamic acid solution is cast into a film and thermally dehydrated and cyclized to obtain a gel film (thermal ring-closure method), or (ii) a method in which a catalyst (cyclization catalyst) and a dehydrating agent (conversion agent) are mixed into the polyamic acid solution and chemically decyclized to produce a gel film, and then heated to obtain a gel film (chemical ring-closure method), with the latter method (chemical ring-closure method) being particularly preferred.

[0105] Surprisingly, the physical properties (characteristics) required for the polyimide film of the present invention can be efficiently obtained by the chemical ring-closure method (or by selecting the above-mentioned polymerization components and the chemical ring-closure method). Also, the chemical ring-closure method is suitable from the viewpoint of mass production.

[0106] The polyamic acid solution may contain a gelation retardant, etc. The gelation retardant is not particularly limited, and acetylacetone, etc., can be used.

[0107] Examples of the cyclization catalyst include amines, such as aliphatic tertiary amines (trimethylamine, triethylenediamine, etc.), aromatic tertiary amines (dimethylaniline, etc.), and heterocyclic tertiary amines (for example, isoquinoline, pyridine, β-picoline, etc.). These may be used alone or in combination of two or more. Among these, heterocyclic tertiary amines such as β-picoline are preferred.

[0108] Examples of the dehydrating agent include acid anhydrides, such as aliphatic carboxylic acid anhydrides (e.g., acetic anhydride, propionic anhydride, butyric anhydride, etc.), and aromatic carboxylic acid anhydrides (e.g., benzoic anhydride, etc.). These may be used alone or in combination of two or more. Among these, acetic anhydride and / or benzoic anhydride are preferred, and acetic anhydride is particularly preferred.

[0109] The amounts of the cyclization catalyst and the dehydrating agent used are not particularly limited, but may be, for example, about 1 mol or more (e.g., 1.5 to 10 mol) per mol of the amide group (or carboxyl group) of the polyamic acid (or polyamic acid).

[0110] The gel film can usually be obtained by casting (coating) a polyamic acid solution (particularly a polyamic acid solution mixed with a cyclization catalyst and a conversion agent) onto a support, and then partially drying and curing (imidization).

[0111] More specifically, the polyamic acid solution may be cast onto a support from a slitted nozzle to form a film, and then heated by receiving heat from the support or a heat source such as hot air or an electric heater to cause a ring-closing reaction. Volatiles such as liberated organic solvents are dried to form a gel film, which can then be peeled off from the support.

[0112] Here, the gel film needs to have self-supporting properties in order to be peeled off, but the gel film obtained by the chemical ring-closing method and the gel film obtained by the thermal ring-closing method usually have very different characteristics. That is, in the chemical ring-closing method, gelation (conversion) can be performed using a catalyst, so a self-supporting gel film (soft or wet gel film) containing a large amount of solvent can be obtained, while in the thermal ring-closing method, a large amount of heat treatment is required to gel (to give it self-supporting properties), and as a result, a relatively hard gel film (with little residual solvent) can be obtained.

[0113] The support is not particularly limited, but examples include a metal (e.g., stainless steel) rotating drum, an endless belt, etc. The temperature of the support is not particularly limited, and may be, for example, 30 to 200°C, preferably 40 to 150°C, and more preferably 50 to 120°C. The temperature of the support can be controlled by (i) a liquid or gas heat transfer medium, or (ii) radiant heat from an electric heater or the like.

[0114] In step (2), the gel film is dried (solvent removed) and then heat-treated. Typically, step (2) may include a step of passing the gel film through a heating furnace (such as a tenter heating furnace) while holding both ends in the width direction, drying the gel film, and then heat-treating the gel film.

[0115] Specifically, the gel film peeled off from the support may be stretched in the conveying direction while controlling the running speed with a rotating roll, although this is not particularly limited. The thickness of the polyimide film may be adjusted by changing the running speed.

[0116] The stretching in the machine direction may be performed at a predetermined temperature (for example, a temperature of 140° C. or lower). The stretching ratio (MDX) is usually 1.05 to 1.9 times, preferably 1.1 to 1.6 times, and more preferably 1.1 to 1.5 times (for example, 1.15 to 1.4 times).

[0117] The drying temperature may be, for example, 210° C. or higher (eg, 213 to 500° C.), preferably 215° C. or higher (eg, 218 to 400° C.), and more preferably 220° C. or higher (eg, 220 to 300° C.).

[0118] Furthermore, drying may be performed while suppressing drying unevenness (variation) in the film width direction. For example, the drying temperature unevenness in the film width direction may be less than 25°C (e.g., 0 to 24°C), preferably 22°C or less (e.g., 1 to 21°C), more preferably 20°C or less (e.g., 2 to 19°C), and particularly preferably 18°C ​​or less (e.g., 3 to 18°C).

[0119] The unevenness in drying temperature can be measured, for example, by taking a number of points at a given interval (for example, 200 mm) along the width direction of the film and measuring the difference (width) between the maximum and minimum values ​​of the drying temperature.

[0120] The gel film (particularly the gel film stretched in the conveying direction) is dried and then heat-treated. The heat treatment temperature is not particularly limited, and may be, for example, 200° C. or higher (e.g., 250 to 600° C.), preferably 300° C. or higher, and more preferably 350° C. or higher.

[0121] As described above, the L value can be efficiently adjusted by adjusting or setting the heat treatment temperature (for example, setting the maximum heating temperature) (and further by combining it with other conditions).

[0122] After drying, the film may be stretched in the width direction. The stretching in the width direction may be performed together with the heat treatment.

[0123] In stretching in the transverse direction, the stretch ratio (TDX) may be, for example, 1.05 to 1.9 times, preferably 1.1 to 1.6 times, and more preferably 1.1 to 1.5 times (for example, 1.15 to 1.4 times).

[0124] The physical properties (characteristics) required for the polyimide film of the present invention may be efficiently adjusted by such stretching and its conditions (and further by combining it with other conditions).

[0125] In this manner, a polyimide film is obtained. The polyimide film thus obtained may be further subjected to an annealing treatment.

[0126] The method of the annealing treatment is not particularly limited, and any known method may be used. The temperature of the annealing treatment is not particularly limited, and may be, for example, 200 to 500° C., preferably 200 to 370° C., and more preferably 210 to 350° C. Specifically, the annealing treatment may be performed by running the film under low tension in a furnace heated to the above temperature range. The tension of the film during running may be, for example, 10 to 50 N / m, and more preferably 20 to 30 N / m.

[0127] The polyimide film (the surface thereof) obtained as described above may be subjected to a plasma treatment. The plasma treatment may be performed on both sides or one side of the polyimide film. As described above, in consideration of adhesion when exposed to conditions such as high temperatures, it may be preferable not to subject the polyimide film to plasma treatment, or to subject the polyimide film to plasma treatment to a small extent.

[0128] The method of the plasma treatment is not particularly limited, and any known method may be used. The processing gas for the plasma processing is not particularly limited, but may include inert gases (e.g., He, Ar, Kr, Xe, Ne, Rn, N, etc.), O, H, O, air, CO, etc. The processing gas may be used alone or in combination of two or more.

[0129] The processing pressure of the plasma treatment is not particularly limited, but may be, for example, 0.1 Pa to 1330 kPa. The treatment intensity (E value) of the plasma treatment is not particularly limited, but is, for example, 50 W·min / m2 More than 75W min / m 2 More than 2000W·min / m 2 Below, 1800W min / m 2 The following may be the case. The processing time of the plasma treatment is not particularly limited, but may be, for example, 1 second to 10 minutes.

[0130] [Uses of polyimide film, metal laminated film, etc.] The polyimide film of the present invention is suitable for lamination with metals (metal layers).

[0131] Such a polyimide film can also be laminated with a metal (metal layer) without an adhesive layer (directly), and is therefore also suitable as a polyimide film for laminating a metal (metal layer) without an adhesive layer (directly).

[0132] Furthermore, a metal (metal layer) can be efficiently laminated (formed) on the polyimide film by metallizing (plating, etc.), so the polyimide film of the present invention is also suitable for metallizing.

[0133] Hereinafter, such a preferable polyimide film will be described together with its mode of use.

[0134] As described above, the polyimide film can be made into a laminated film by laminating a metal (metal layer).

[0135] Such a laminated film can be called a laminated film (metal-laminated polyimide film, metal-laminated film) composed of a polyimide film and a metal layer (metal) laminated on the polyimide film.

[0136] In the laminated film, the metal layer may be laminated (formed) on the polyimide film, usually without an adhesive layer (or directly).

[0137] In such a laminate film, the metal layer may be a metal foil or the like, or may be formed by metallizing, and is preferably formed by metallizing.

[0138] The metallizing (metallizing method) is not particularly limited, but a representative example is plating (plating method). Specific examples of metallizing include wet plating (e.g., electrolytic plating) and dry plating (e.g., vacuum deposition, sputtering, ion plating, etc.).

[0139] These methods may be used alone or in combination of two or more. For example, when the metal layer is composed of an underlayer and an overlayer as described below, the underlayer may be formed by a dry plating method (for example, relatively thin) and the overlayer may be formed by a wet plating method.

[0140] The metal constituting the metal layer is not particularly limited, but examples thereof include metals such as copper, nickel, chromium, manganese, aluminum, iron, molybdenum, cobalt, tungsten, vanadium, titanium, and talc, alloys of these metals, oxides of these metals, and carbides of these metals.

[0141] The metal layer may be made of one or more metals.

[0142] The metal layer may be a single layer or multiple layers (for example, 2 to 3 layers).

[0143] For example, the metal layer may be composed of an underlayer (underlayer metal layer, base metal layer) and an overlayer (overlayer metal layer, wiring layer) laminated (formed) on the underlayer. The underlayer and overlayer (e.g., underlayer) may also be multi-layered.

[0144] When the metal layer is multi-layered, the metals constituting each layer may be the same or different.

[0145] For example, in the case of a copper laminated film, the metal layer in the copper laminated film may be composed of only a copper layer, or the copper layer (upper layer) may be formed via an underlayer (underlying metal layer). In this case, the underlayer may be one layer or two or more layers, and may be composed of at least one type selected from copper and non-copper metals.

[0146] Specific examples of metal layers having a copper layer as an upper layer include an underlayer (e.g., a sputtering layer) made of at least one layer selected from a copper layer, a non-copper metal layer (e.g., a nickel / chromium layer), and combinations thereof, and a copper layer (e.g., a plating layer) laminated on this underlayer.

[0147] The metal layer may be formed on one side or both sides of the polyimide film. When a plasma-treated polyimide film is used, the metal layer may be formed on the plasma-treated side of the polyimide film.

[0148] The thickness of the metal layer (total thickness if multi-layered, thickness of each metal layer if provided on both sides) can be appropriately selected depending on the application and the form of the metal layer, and may be 1 nm or more (e.g., 2 nm to 100 μm), 3 nm or more (e.g., 5 nm to 50 μm), etc.

[0149] In particular, in wiring boards (printed wiring boards) and the like, the thickness of a metal layer [for example, a copper layer (including a metal layer having a copper layer as an upper layer)] may be 1 μm or more (for example, 1 to 50 μm, 2 to 40 μm), preferably 3 μm or more (for example, 3 to 30 μm, 4 to 25 μm, 3 to 20 μm), and more preferably 5 μm or more (for example, 5 to 30 μm, 5 to 20 μm, 5 to 15 μm), etc.

[0150] When the metal layer includes an underlayer, the thickness of the underlayer is not particularly limited, and may be, for example, 1 to 500 nm (eg, 5 to 200 nm).

[0151] When the metal layer includes an underlayer, the proportion of the thickness of the underlayer to the total thickness of the metal layer may be selected from a range of, for example, approximately 30% or less, and may be 20% or less (e.g., 15% or less, 10% or less, 5% or less, 3% or less, 2% or less), etc.

[0152] In particular, the thickness of the metal layer may be relatively small (thin), for example, 50 μm or less (e.g., 40 μm or less), preferably 30 μm or less (e.g., 25 μm or less), and more preferably 20 μm or less (e.g., 15 μm or less, 12 μm or less, 10 μm or less).

[0153] According to the polyimide film of the present invention (the laminated film of the present invention), even with such a metal layer having a relatively small (thin, low proportion) thickness, sufficient adhesion can be achieved.

[0154] In the laminated film, the thickness ratio of the polyimide film to the metal layer can be selected depending on the application, etc., and may be selected, for example, from a range of about polyimide film / metal layer (thickness ratio) = 1 / 0.001 to 1 / 100 (e.g., 1 / 0.01 to 1 / 50), and may be about 1 / 0.02 to 1 / 10 (e.g., 1 / 0.03 to 1 / 8), preferably 1 / 0.05 to 1 / 5 (e.g., 1 / 0.07 to 1 / 3), and more preferably 1 / 0.1 to 1 / 2 (e.g., 1 / 0.15 to 1 / 1, 1 / 0.2 to 1 / 0.8). According to the polyimide film of the present invention (the laminated film of the present invention), even with such a thickness ratio, the polyimide film can fully exhibit its function as a base film.

[0155] Taking a copper laminated film (e.g., a copper laminated film suitable for printed wiring boards, etc.) as an example, a more specific example (specific example) of the manufacturing method can be mentioned, in which the surface of a polyimide film on which copper is to be formed is subjected to a base treatment under vacuum conditions (e.g., base treatment with nickel / chromium is performed by sputtering, followed by sputtering with copper) to form a thin copper film, and then a copper layer is laminated by electrolytic plating using a copper sulfate bath or the like.

[0156] The metal layer (copper plating layer, etc.) may be patterned by etching, etc. The etching method is not particularly limited, and any conventionally known method may be used.

[0157] In the laminated film, the metal layer and the polyimide film may be firmly adhered to each other.

[0158] Examples of such laminated films include those having a peel strength (adhesion strength, peel strength) value (T1) between the metal layer and the polyimide film of more than 0.4 kN / m (e.g., 0.45 kN / m or more), preferably 0.5 kN / m or more (e.g., 0.55 kN / m or more), more preferably 0.6 kN / m or more (e.g., 0.65 kN / m or more), particularly preferably 0.7 kN / m or more (e.g., 0.75 kN / m or more), and particularly preferably 0.8 kN / m or more (e.g., more than 0.8 kN / m, 0.85 kN / m or more, 0.9 kN / m or more).

[0159] The upper limit of T1 is not particularly limited, but may be, for example, 5 kN / m or less, 4 kN / m or less, 3 kN / m or less, 2.5 kN / m or less, 2 kN / m or less, 1.5 kN / m or less, 1.2 kN / m or less, 1 kN / m or less, etc.

[0160] Such adhesion can be maintained at a relatively high level even under conditions such as high temperatures (e.g., severe conditions), etc. Examples of such laminated films include laminated films in which, when the peel strength (adhesion, peel strength) between the metal layer and the polyimide film is T1 and the peel strength (adhesion, peel strength) between the metal layer and the polyimide film after heating at 150°C for 168 hours is T2, T2 / T1 is 0.3 or more (e.g., 0.4 or more), preferably 0.5 or more (e.g., more than 0.5, 0.55 or more), more preferably 0.6 or more (e.g., 0.65 or more), particularly 0.7 or more (e.g., 0.72 or more), and particularly preferably 0.75 or more (e.g., more than 0.75, 0.78 or more, 0.8 or more).

[0161] The upper limit of T2 / T1 may be 1 or less than 1 (for example, 0.99 or less, 0.98 or less, 0.97 or less, 0.96 or less, 0.95 or less, 0.94 or less, 0.93 or less, 0.92 or less, 0.91 or less, 0.9 or less).

[0162] The value of T2 may be, for example, greater than 0.3 kN / m (e.g., 0.35 kN / m or more), preferably 0.4 kN / m or more (e.g., 0.45 kN / m or more), more preferably 0.5 kN / m or more (e.g., 0.55 kN / m or more), particularly 0.6 kN / m or more (e.g., 0.65 kN / m or more), and particularly preferably 0.7 kN / m or more (e.g., greater than 0.7 kN / m, 0.75 kN / m or more, 0.8 kN / m or more).

[0163] The upper limit of T2 is not particularly limited, but may be, for example, 5 kN / m or less, 4 kN / m or less, 3 kN / m or less, 2.5 kN / m or less, 2 kN / m or less, 1.5 kN / m or less, 1.2 kN / m or less, 1 kN / m or less, 0.9 kN / m or less, 0.8 kN / m or less, etc.

[0164] The method for measuring T1 (and further T2) may be, for example, a method conforming to Method A in the copper foil peel strength test method described in JIS C 6471 (for example, a pulling angle of 90° and a pulling speed of 50 mm / min). More specifically, T1 (and further T2) may be measured by the method described in the Examples below.

[0165] The laminated film can be used for various applications, for example, in circuit boards (particularly boards using fine-pitch wiring circuits) such as COF (chip on film) and flexible printed circuit boards (FPC). EXAMPLES

[0166] Next, the present invention will be described in more detail with reference to examples. However, the present invention is not limited to these examples, and many modifications can be made by those skilled in the art within the technical spirit of the present invention.

[0167] In the examples, the following compounds are represented by the following abbreviations: Paraphenylenediamine: PPD 4,4'-Diaminodiphenyl ether: 4,4'-ODA: 1,3-Bis(3-aminophenoxy)benzene: RODA Pyromellitic dianhydride: PMDA 3,3',4,4'-Biphenyltetracarboxylic dianhydride: BPDA N,N-Dimethylacetamide: DMAc

[0168] The characteristics were evaluated by the following methods.

[0169] Dynamic Viscoelasticity The equipment used was DMS6100 (product name: manufactured by Hitachi High-Tech Science), and the measurement was performed in the temperature range of 25 to 420°C, with a nitrogen flow rate of 50 mL / min, a heating rate of 2°C / min, and a measurement frequency of 5 Hz. The temperature at which the loss tangent tan δ (E″ / E′), which is the ratio of the loss modulus (E”) to the storage modulus (E′), obtained by the measurement, shows a maximum was defined as the glass transition temperature (Tg).

[0170] Coefficient of Thermal Expansion (CTE) The measurement was performed using a device: TMA-50 (trade name, manufactured by Shimadzu Corporation) at a measurement temperature range of 50 to 200° C. and a heating rate of 10° C. / min. The thermal expansion coefficient α was defined as α=(αMD+αTD) / 2, where αMD is the linear expansion coefficient in the machine direction (MD) of the film and αTD is the linear expansion coefficient in the width direction (TD).

[0171] Film thickness Using a Mitutoyo Litematic (Series 318) thickness gauge, 15 locations were randomly selected from the front surface of the film, and the thickness was measured at these 15 locations, and the average was calculated to obtain the film thickness.

[0172] -Thermal compression displacement A WALTS TEG chip "WALTS-TEG LCD30A-0101JY" was placed on the sample, and the head part, whose surface temperature was 400°C, was thermocompressed from above with a pressure of 44 N for 1 second. The height of the unevenness generated on the sample surface was measured with a VK-9710 (product name: KEYNCE color 3D laser microscope) and defined as the thermocompression displacement.

[0173] L value Using the "SM7 Color Computer model SM-7 Ver 1.00" manufactured by Suga Test Instruments Co., Ltd., the following conditions were selected for each measurement, and the polyimide film was placed on the sample stage and measured. Optical system: 2 optical path optical system reflection Light source / field of view: C light 2° field of view Display selection: Lab After measurement, L, a, and b are automatically printed, and the L value was treated as the L value.

[0174] ·Dimensional stability The dimensional stability of the film was evaluated according to the following criteria. A: Extremely small dimensional change during sputtering, plating and / or etching B: Slight dimensional change during sputtering, plating and / or etching C: Large dimensional changes during sputtering, plating and / or etching D: Dimensional changes are extremely large during sputtering, plating and / or etching.

[0175] Adhesion strength between copper and polyimide film (90° peel strength) The adhesion strength between copper and polyimide film in the copper-laminated polyimide film was measured in accordance with Method A of the copper foil peel strength test method described in JIS C 6471, at a pulling angle of 90° and a pulling speed of 50 mm / min. The adhesion strength measured immediately after the copper-laminated polyimide film was prepared was defined as normal adhesion strength (T1), and the adhesion strength measured after heating at 150° C. for 168 hours was defined as heat-resistant adhesion strength (T2).

[0176] Evaluation of inorganic particles A sample dispersed in a polar solvent was measured using a laser diffraction / scattering particle size distribution analyzer LA-910 manufactured by Horiba, Ltd., and the results of analyzing the laser diffraction and scattered light intensity patterns were used to read the volume average diameter, particle size range, average particle diameter, and the occupancy rate of particles of a specific particle size relative to all particles.

[0177] [Synthesis Example 1] 21.7g of PPD was placed in a 2000mL separable flask, 960g of DMAc was added, and the mixture was stirred until completely dissolved. 42.4g of PMDA was added and stirred for 1 hour. 88.0g of RODA was then added, and after confirming that it was completely dissolved, 81.1g of BPDA and 4.2g of PMDA were added and stirred for 3 hours to obtain a solution. To the obtained solution (polyamic acid solution), an N,N-dimethylacetamide slurry of calcium hydrogen phosphate (average particle diameter 0.87 μm, the proportion of particles with particle diameters of 0.5 to 2.5 μm was 81.5 vol% of the total particles) was added so that the proportion of calcium hydrogen phosphate in the polyimide (film) was 0.15 mass%, and the mixture was thoroughly stirred and dispersed to obtain a polyamic acid solution containing inorganic particles [a 3000 poise solution (solid content 20 wt%)].

[0178] [Synthesis Example 2] 11.5g of PPD was placed in a 2000mL separable flask, 960g of DMAc was added, and the mixture was stirred until completely dissolved. 22.4g of PMDA was added and the mixture was stirred for 1 hour. 84.8g of 4,4'-ODA was then added, and after confirming that it was completely dissolved, 109.1g of BPDA and 11.1g of PMDA were added and the mixture was stirred for 3 hours to obtain a solution. To the obtained solution (polyamic acid solution), an N,N-dimethylacetamide slurry of calcium hydrogen phosphate (average particle diameter 0.87 μm, the proportion of particles with particle diameters of 0.5 to 2.5 μm was 81.5 vol% of the total particles) was added so that the proportion of calcium hydrogen phosphate in the polyimide (film) was 0.12 mass%, and the mixture was thoroughly stirred and dispersed to obtain a polyamic acid solution containing inorganic particles [a 3000 poise solution (solid content 20 wt%)].

[0179] [Synthesis Example 3] 97.2 g of 4,4'-ODA was placed in a 2000 mL separable flask, 960 g of DMAc was added thereto, and the mixture was stirred until completely dissolved. 141.4 g of BPDA was then added, and the mixture was stirred for 3 hours to obtain a solution. To the obtained solution (polyamic acid solution), an N,N-dimethylacetamide slurry of calcium hydrogen phosphate (average particle diameter 0.87 μm, the proportion of particles with particle diameters of 0.5 to 2.5 μm was 81.5 vol% of the total particles) was added so that the proportion of calcium hydrogen phosphate in the polyimide (film) was 0.2 mass%, and the mixture was thoroughly stirred and dispersed to obtain a polyamic acid solution containing inorganic particles [a 2700 poise solution (solids content 20 wt%)].

[0180] [Synthesis Example 4] 25.7g of PPD was placed in a 2000mL separable flask, 960g of DMAc was added, and the mixture was stirred until completely dissolved. 50.2g of PMDA was added and the mixture was stirred for 1 hour. 71.3g of 4,4'-ODA was then added, and after confirming that it was completely dissolved, 52.4g of BPDA and 39.1g of PMDA were added and the mixture was stirred for 3 hours to obtain a solution. To the obtained solution (polyamic acid solution), an N,N-dimethylacetamide slurry of silica (average particle diameter 1.1 μm, the proportion of particles with particle diameters of 0.5 to 2.5 μm was 90 volume % of the total particles) was added so that the proportion of silica in the polyimide (film) was 0.15 mass %, and the mixture was thoroughly stirred and dispersed to obtain a polyamic acid solution containing inorganic particles [a 3000 poise solution (solid content 20 weight %)].

[0181] [Synthesis Example 5] 64.5 g of PPD was placed in a 2000 mL separable flask, 960 g of DMAc was added thereto, and the mixture was stirred until completely dissolved. 173.7 g of BPDA was then added, and the mixture was stirred for 3 hours to obtain a solution. To the obtained solution (polyamic acid solution), an N,N-dimethylacetamide slurry of silica (average particle diameter 1.1 μm, the proportion of particles with particle diameters of 0.5 to 2.5 μm was 90 volume % of the total particles) was added so that the proportion of silica in the polyimide (film) was 0.9 mass %, and the mixture was thoroughly stirred and dispersed to obtain a polyamic acid solution containing inorganic particles [a 3200 poise solution (solid content 20 weight %)].

[0182] [Example 1] After cooling 100 parts by weight of the polyamic acid solution obtained in Synthesis Example 1 to -5°C, 25 parts by weight of DMAc, 84 parts by weight of acetic anhydride, and 74 parts by weight of beta-picoline were mixed, extruded from a T-die with a nozzle slit width of 1.3 mm, and cast onto a rotating metal support at 73°C to obtain a self-supporting gel film. This gel film was continuously peeled off from the metal support, and transported by a roll in a room at 70°C while being stretched 1.25 times in the film longitudinal direction. While pressing both ends of the gel film with rollers, the gel film was fixed by continuously piercing it into pin plates on a chain, and 250°C air was blown onto the pin plate for 10 to 15 seconds to dry and fix the gel film ends first. The gel film, both ends of which were fixed on a pin plate with pins, was stretched 1.54 times in the width direction, then dried in a tenter by blowing 250°C air onto it for about 50 seconds, and then heat-treated for about 80 seconds using an electric heater so that the film surface temperature reached 410°C, after which it was cooled to room temperature while being relaxed. The ends of the film were then removed from the pins, and the edges of the film ends were cut to obtain a polyimide film with a width of 2290 mm and a thickness of 25 μm.

[0183] The properties of this film (or the polyimide constituting the film) were evaluated, and the results are shown in Table 1.

[0184] Next, a 25 nm thick nickel / chromium alloy (nickel / chromium = 80 / 20) layer was formed on the surface (both sides) of the obtained polyimide film by sputtering. Next, a 100 nm thick copper layer was formed on this nickel / chromium alloy layer by the same sputtering method. Next, the copper layer was made 8.5 μm thick by electrolytic copper plating. Finally, a copper laminated polyimide film was obtained by patterning by copper etching so that the wiring width was 1 mm. The adhesion of this copper laminated film was evaluated, and the results are shown in Table 1.

[0185] [Example 2] After cooling 100 parts by weight of the polyamic acid solution obtained in Synthesis Example 1 to -5°C, 25 parts by weight of DMAc, 80 parts by weight of acetic anhydride, and 70 parts by weight of beta-picoline were mixed, extruded from a T-die with a nozzle slit width of 1.3 mm, and cast onto a rotating metal support at 72°C to obtain a self-supporting gel film. This gel film was continuously peeled off from the metal support, and transported by a roll in a room at 70°C while being stretched 1.25 times in the film longitudinal direction. While pressing both ends of the gel film with rollers, the gel film was fixed by continuously piercing it into pin plates on a chain, and 250°C air was blown onto the pin plate for 10 to 20 seconds to dry and fix the gel film ends first. The gel film, both ends of which were fixed on a pin plate, was stretched 1.45 times in the width direction, and then dried in a tenter by blowing 250°C air onto it for about 60 seconds. Then, the film was heat-treated for about 90 seconds using an electric heater so that the film surface temperature reached 410°C, and then cooled to room temperature while relaxing. The ends of the film were then removed from the pins, and the edges of the ends of the film were cut to obtain a polyimide film with a width of 2160 mm and a thickness of 30 μm. The properties of this film (or the polyimide constituting the film) were evaluated, and the results are shown in Table 1. Furthermore, using this film, a copper laminated film was obtained in the same manner as in Example 1, and the adhesion was evaluated. The results are shown in Table 1.

[0186] [Example 3] After cooling 100 parts by weight of the polyamic acid solution obtained in Synthesis Example 1 to -5°C, 28 parts by weight of DMAc, 70 parts by weight of acetic anhydride, and 63 parts by weight of beta-picoline were mixed, extruded from a T-die with a nozzle slit width of 1.3 mm, and cast onto a rotating metal support at 70°C to obtain a self-supporting gel film. This gel film was continuously peeled off from the metal support, and transported by a roll in a room at 70°C while being stretched 1.25 times in the film longitudinal direction. While pressing both ends of the gel film with rollers, the gel film was fixed by continuously piercing it into pin plates on a chain, and 250°C air was blown onto the pin plate for 15 to 25 seconds to dry and fix the gel film ends first. The gel film, both ends of which were fixed on a pin plate, was stretched 1.46 times in the width direction, and then dried in a tenter by blowing 250°C air for about 70 seconds. Then, the film was heat-treated for about 120 seconds using an electric heater so that the film surface temperature reached 410°C, and then cooled to room temperature while relaxing. The ends of the film were then removed from the pins, and the edges of the film ends were cut to obtain a polyimide film with a width of 2200 mm and a thickness of 38 μm. The properties of this film (or the polyimide constituting the film) were evaluated, and the results are shown in Table 1. Furthermore, using this film, a copper laminated film was obtained in the same manner as in Example 1, and the adhesion was evaluated. The results are shown in Table 1.

[0187] [Example 4] After cooling 100 parts by weight of the polyamic acid solution obtained in Synthesis Example 2 to -5°C, 30 parts by weight of DMAc, 75 parts by weight of acetic anhydride, and 67 parts by weight of beta-picoline were mixed, extruded from a T-die with a nozzle slit width of 1.3 mm, and cast onto a rotating metal support at 70°C to obtain a self-supporting gel film. This gel film was continuously peeled off from the metal support, and transported by a roll in a room at 70°C while being stretched 1.25 times in the film longitudinal direction. While pressing both ends of the gel film with rollers, the gel film was fixed by continuously piercing it into pin plates on a chain, and 250°C air was blown onto the pin plate for 15 to 25 seconds to dry and fix the gel film ends first. The gel film, both ends of which were fixed on a pin plate, was stretched 1.46 times in the width direction, and then dried in a tenter by blowing 250°C air for about 70 seconds. Then, the film was heat-treated for about 120 seconds using an electric heater so that the film surface temperature reached 410°C, and then cooled to room temperature while relaxing. The ends of the film were then removed from the pins, and the edges of the film ends were cut to obtain a polyimide film with a width of 2200 mm and a thickness of 38 μm. The properties of this film (or the polyimide constituting the film) were evaluated, and the results are shown in Table 1. Furthermore, using this film, a copper laminated film was obtained in the same manner as in Example 1, and the adhesion was evaluated. The results are shown in Table 1.

[0188] [Example 5] After cooling 100 parts by weight of the polyamic acid solution obtained in Synthesis Example 1 to -5°C, 32 parts by weight of DMAc, 80 parts by weight of acetic anhydride, and 70 parts by weight of beta-picoline were mixed, extruded from a T-die with a nozzle slit width of 1.3 mm, and cast onto a rotating metal support at 76°C to obtain a self-supporting gel film. This gel film was continuously peeled off from the metal support, and transported by a roll in a room at 70°C while being stretched 1.25 times in the film longitudinal direction. While pressing both ends of the gel film with rollers, the gel film was fixed by continuously piercing it into pin plates on a chain, and 250°C air was blown onto the pin plate for 15 to 25 seconds to dry and fix the gel film ends first. The gel film, both ends of which were fixed on a pin plate, was stretched 1.47 times in the width direction, and then dried in a tenter by blowing 250°C air for about 70 seconds. Then, the film was heat-treated for about 120 seconds using an electric heater so that the film surface temperature reached 410°C, and then cooled to room temperature while relaxing. The ends of the film were then removed from the pins, and the edges of the film ends were cut to obtain a polyimide film with a width of 2125 mm and a thickness of 43 μm. The properties of this film (or the polyimide constituting the film) were evaluated, and the results are shown in Table 1. Furthermore, using this film, a copper laminated film was obtained in the same manner as in Example 1, and the adhesion was evaluated. The results are shown in Table 1.

[0189] [Example 6] After cooling 100 parts by weight of the polyamic acid solution obtained in Synthesis Example 1 to -5°C, 38 parts by weight of DMAc, 97 parts by weight of acetic anhydride, and 73 parts by weight of beta-picoline were mixed, extruded from a T-die with a nozzle slit width of 1.3 mm, and cast onto a rotating metal support at 66°C to obtain a self-supporting gel film. This gel film was continuously peeled off from the metal support, and transported by a roll in a room at 70°C while being stretched 1.25 times in the film longitudinal direction. While pressing both ends of the gel film with rollers, the gel film was fixed by continuously piercing it into pin plates on a chain, and 250°C air was blown onto the pin plate for 20 to 30 seconds to dry and fix the gel film ends first. The gel film, both ends of which were fixed on a pin plate, was stretched 1.47 times in the width direction, and then dried in a tenter by blowing 250°C air for about 100 seconds. Then, the film was heat-treated for about 160 seconds using an electric heater so that the film surface temperature reached 410°C, and then cooled to room temperature while relaxing. The ends of the film were then removed from the pins, and the edges of the film ends were cut to obtain a polyimide film with a width of 2165 mm and a thickness of 50 μm. The properties of this film (or the polyimide constituting the film) were evaluated, and the results are shown in Table 1. Furthermore, using this film, a copper laminated film was obtained in the same manner as in Example 1, and the adhesion was evaluated. The results are shown in Table 1.

[0190] [Example 7] 100 parts by weight of the polyamic acid solution obtained in Synthesis Example 3 was cooled to -5°C, and then 13.4 parts by weight of β-picoline, 13.2 parts by weight of acetic anhydride, and 5.9 parts by weight of DMAc were added thereto, and the mixture was cast onto a glass plate using an applicator to obtain a self-supporting gel film. The obtained gel film (unstretched film) was set in a biaxial stretching machine with clips, and stretched stepwise to 1.1 times in the longitudinal direction (transport direction), and then 1.1 times in the transverse direction (width direction). The stretched gel film was pinned to a metal frame with 10 cm square needles, and heat-treated under conditions of 200°C for 30 minutes, 300°C for 20 minutes, 360°C for 4 minutes, and 410°C for 1 minute to obtain a 38 μm thick polyimide film (sequentially biaxially stretched film). The properties of this film (or the polyimide constituting the film) were evaluated, and the results are shown in Table 1. Furthermore, using this film, a copper laminated film was obtained in the same manner as in Example 1, and the adhesion was evaluated. The results are shown in Table 1.

[0191] [Example 8] A polyimide film was produced in the same manner as in Example 3 (Example 1), except that the film surface temperature was changed to 360° C., and the properties and the like were evaluated. Furthermore, using this film, a copper laminated film was obtained in the same manner as in Example 3 (Example 1), and the adhesion was evaluated.

[0192] [Comparative Example 1] After cooling 100 parts by weight of the polyamic acid solution obtained in Synthesis Example 4 to -5°C, 32 parts by weight of DMAc, 85 parts by weight of acetic anhydride, and 75 parts by weight of beta-picoline were mixed, extruded from a T-die with a nozzle slit width of 1.3 mm, and cast onto a rotating metal support at 70°C to obtain a self-supporting gel film. This gel film was continuously peeled off from the metal support, and transported by a roll in a room at 70°C while being stretched 1.25 times in the film longitudinal direction. While pressing both ends of the gel film with rollers, the gel film was fixed by continuously piercing it into pin plates on a chain, and 250°C air was blown onto the pin plate for 15 to 25 seconds to dry and fix the gel film ends first. The gel film, both ends of which were fixed on a pin plate, was stretched 1.46 times in the width direction, and then dried in a tenter by blowing 250°C air for about 70 seconds. Then, the film was heat-treated for about 120 seconds using an electric heater so that the film surface temperature reached 410°C, and then cooled to room temperature while relaxing. The ends of the film were then removed from the pins, and the edges of the film ends were cut to obtain a polyimide film with a width of 2200 mm and a thickness of 38 μm. The properties of this film (or the polyimide constituting the film) were evaluated, and the results are shown in Table 1. Furthermore, using this film, a copper laminated film was obtained in the same manner as in Example 1, and the adhesion was evaluated. The results are shown in Table 1.

[0193] [Comparative Example 2] A polyimide film was prepared in the same manner as in Example 7, except that the polyamic acid solution obtained in Synthesis Example 5 was used, and the properties and the like were evaluated. Furthermore, using this film, a copper laminated film was obtained in the same manner as in Example 1, and the adhesion was evaluated. The results are shown in Table 1.

[0194] [Table 1] [Industrial Applicability]

[0195] The polyimide film of the present invention is useful for laminating metals, etc.

Claims

1. A polyimide film for metal lamination, having a glass transition temperature of 300°C or less.

2. 2. The polyimide film according to claim 1, which has a glass transition temperature of 180 to 290°C.

3. 2. The polyimide film according to claim 1, which has a loss tangent at its glass transition temperature of 0.85 or less.

4. 2. The polyimide film according to claim 1, wherein the ratio E'(Tg+30°C) / E'(30°C) of the storage modulus E'(30°C) at 30°C to the storage modulus E'(Tg+30°C) at Tg+30°C is 0.02 or more.

5. 2. The polyimide film according to claim 1, wherein the value of (αMD+αTD) / 2 is 20 ppm / K or less, where αMD is the linear expansion coefficient in the MD direction and αTD is the linear expansion coefficient in the TD direction.

6. 2. The polyimide film according to claim 1, wherein the absolute value of the difference between αMD and αTD (αMD-αTD) is 10 ppm / K or less, where αMD is the linear expansion coefficient in the MD direction and αTD is the linear expansion coefficient in the TD direction.

7. 2. The polyimide film according to claim 1, which has a height of 3 μm or less on the film surface when the film surface is thermocompressed at a temperature of 400° C. and a pressure of 44 N for 1 second.

8. The glass transition temperature is 200 to 280° C. The loss tangent at the glass transition temperature is 0.75 or less, the ratio E'(Tg+30°C) / E'(30°C) of the storage modulus E'(30°C) at 30°C to the storage modulus E'(Tg+30°C) at Tg+30°C is 0.04 or more; When the linear expansion coefficient in the MD direction is αMD and the linear expansion coefficient in the TD direction is αTD, the value of (αMD+αTD) / 2 is 2 to 18 ppm / K, and the absolute value of the difference between αMD and αTD (αMD-αTD) is 7 ppm / K or less, When the film surface is thermocompressed at a temperature of 400° C. and a pressure of 44 N for 1 second, the height of the irregularities generated on the film surface is 2.5 μm or less. Polyimide film for metal lamination.

9. 2. The polyimide film according to claim 1, wherein when a copper layer is directly laminated thereon, the peel strength T1 between the copper layer and the polyimide film is 0.5 kN / m or more.

10. 2. The polyimide film according to claim 1, wherein T1 is the peel strength between the copper layer and the polyimide film when the copper layer is directly laminated thereon, and T2 is the peel strength between the copper layer and the polyimide film after heating at 150° C. for 168 hours. T1 is 0.5 kN / m or more, and T2 / T1 is 0.6 or more.

11. When the thickness is 28 μm or less, the L value is 65 or more, When the thickness is more than 28 μm and not more than 35 μm, the L value is 60 to 70; When the thickness is more than 35 μm and not more than 40 μm, the L value is 58 to 68; When the thickness is more than 40 μm and not more than 48 μm, the L value is 56 to 66; 2. The polyimide film according to claim 1, wherein the L value is 63 or less when the thickness is more than 48 μm.

12. The polyimide film according to claim 1, comprising as polymerization components an aromatic diamine component containing at least one selected from 1,3-bis(3-aminophenoxy)benzene, paraphenylenediamine, and 4,4'-diaminodiphenyl ether, and an aromatic acid anhydride component containing at least one selected from pyromellitic dianhydride and 3,3',4,4'-biphenyltetracarboxylic dianhydride.

13. 2. The polyimide film according to claim 1, wherein 1,3-bis(3-aminophenoxy)benzene is at least a polymerization component (a diamine component containing 1,3-bis(3-aminophenoxy)benzene is a polymerization component).

14. The polyimide film according to claim 1 , which contains inorganic particles.

15. The polyimide film of claim 1 , which is in a roll form.

16. 2. The polyimide film according to claim 1, which contains 0.01 to 5% by mass of inorganic particles and is in the form of a roll having a length of 5 m or more.

17. 2. The polyimide film according to claim 1, which is for metallizing.

18. 2. The polyimide film according to claim 1, for directly laminating a copper layer having a thickness of 20 μm or less.

19. A laminated film comprising a polyimide film and a metal layer laminated directly on the polyimide film, the polyimide film being the polyimide film according to any one of claims 1 to 18.

20. 20. The laminated film according to claim 19, wherein the metal layer is a copper layer having a thickness of 20 μm or less.

21. 20. The laminated film according to claim 19, wherein the peel strength T1 between the metal layer and the polyimide film is 0.5 kN / m or more.

22. The laminated film according to claim 19, wherein T1 is a peel strength between the metal layer and the polyimide film, and T2 is a peel strength between the metal layer and the polyimide film after heating at 150°C for 168 hours, T1 is 0.5 kN / m or more, and T2 / T1 is 0.6 or more.

Citation Information

Patent Citations

  • flexible printed circuit board

    JP2680816B2